2011
DOI: 10.1159/000330638
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Regression of Leukoaraiosis after Carotid Artery Revascularization

Abstract: Background: Leukoaraiosis (LA) affects cognition after stroke and reversal of LA may improve cognitive performance. We aimed to determine the impact of cerebral perfusion and circle of Willis (CoW) flow patterns on the extent of LA after carotid artery revascularization. Methods: LA was scored on fluid-attenuated inversion recovery magnetic resonance (MR) images at the levels of the centrum semiovale and frontal horns in both cerebral hemispheres of 62 contiguous patients (men/women = 38/24, mean age = 63.2 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
(43 reference statements)
0
10
1
2
Order By: Relevance
“…However, the correlation of leukoaraiosis with cerebral atherosclerosis is not ascertained, and conflicting conclusions have been reported. [16][17]19,21 In our study, we did not find the association between the severe carotid atherosclerosis and WMLs in periventricular and deep white matter. The results supported that WMLs are not correlated with atherosclerosis and may be one type of small-vessel disease.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…However, the correlation of leukoaraiosis with cerebral atherosclerosis is not ascertained, and conflicting conclusions have been reported. [16][17]19,21 In our study, we did not find the association between the severe carotid atherosclerosis and WMLs in periventricular and deep white matter. The results supported that WMLs are not correlated with atherosclerosis and may be one type of small-vessel disease.…”
Section: Discussioncontrasting
confidence: 72%
“…5,19,20 Recent study even indicated that carotid artery revascularization could reduce the severity of leukoaraiosis. 21 Chronic cerebral hypoperfusion due to arterial stenosis may be the underlying mechanism of WMLs. It also could induce the collateralization.…”
mentioning
confidence: 99%
“…Restoration of cerebral perfusion by carotid revascularization can reduce the severity of leukoaraiosis [18]. Although the OA flow direction is sensitive to the overall cerebral perfusion condition, whether the reconstitution of cerebral perfusion through reversed OA flow is adequate to maintain cognitive function or can be employed as a surrogate marker of cognitive impairment remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Когнитивная послеоперационная дисфункция -од-на из серьезнейших проблем современной реабилитации пациентов после кардиохирургических и сосудистых опе-раций во всем мире [4,[7][8][9][10]. Операции на дуге аорты (ДА) выполняют по жизненным показаниям при абсо-лютной бесперспективности консервативного лечения, в то время как хирургия брахицефальных артерий (БА) при-звана сократить частоту фатального и грубого очагового поражения центральной нервной системы (ЦНС).…”
unclassified
“…Y. Chuang и соавт. [10] с по-мощью МРТ и ангиографии сравнили размеры зон лейко-ареоза у 62 пациентов, перенесших инсульт ГМ, до стен-тирования и в ближайшем послеоперационном периоде. Авторы выявили зависимость замкнутости виллизиева круга на факт развития инсульта у пациентов с унилате-ральным стенозом внутренней сонной артерии, а также продемонстрировали, что уменьшение старых зон лейко-ареоза происходит сразу после операции.…”
unclassified